A Preliminary Study on Industrial Safety Management in Malaysia: The Viewpoints of Safety Experts and Practitioners - Azizan, Ramli; Mazlin, Mokhtar; Badhrulhisham, Abdul Aziz (AENSI, 2014)
After independent in 1957, Malaysia economy has moved from agricultural based commodity to middle income economy. However, the economy development and industrialization sometimes predominates over workers and societal needs for safer and healthier life. Due to the complexity of industrial process and use of hazardous chemicals, hazards to cause harms in future seem to be unpredictable and frightening. Indeed, the implementation of an effective safety management is of paramount importance. Thus, this article discusses the result of an open-ended interview with safety experts and practitioners on the current practice of safety management in Malaysia. The interview was focused on four factors, namely, organization, institution, legislation, and technology. These factors are selected due to the fact that they are closely relevant to the local condition and local instruments. The group of respondents in this study consists of respective personnel from various organizations such as industry, government agencies, academic institution, and nongovernmental organization (NGO’s). Objective: The purpose of this paper is to provide researchers, government agencies and independent bodies an overview on industrial safety management in Malaysia from the viewpoints of safety experts and practitioners. In addition, this paper will also highlight the respondent’s initial opinions towards the establishment of cooperative network for safety management in the context of Malaysia’s industrial estate. Results: From the overall interview’s result, the management commitment and awareness, strengthening the legal mechanism and institutional structure, and encouraging the use and development of safety-embedded technology are among the concerns that need to be focused on. In addition to this, the financial support also plays a vital role in order to assist industry to further improve their safety management practice. Furthermore, the respondents have also responded to the idea of establishing a cooperative relationship to further enhance the safety management at the macro level of industrial estate instead of at the individual firm. Most of them basically agreed with the approach whereby it is an innovative step towards betterment of safety management system. Conclusion: These findings are based on experts and practitioner’s opinion and their personal’s point of views. Therefore, from this result, further exploration is unavoidable and in-depth study ought to be carried out in order to come out with a clearer picture. Besides, in relation to the establishment of cooperative network for safety management, this approach is not straightforward and we need to look at several issues and obstacles which may hinder this movement. This is due to the fact that Malaysia has the uniqueness in term of its multi-ethnic culture, political status quo, legislations, technological strength and readiness of industry to partake in this initiative. Thus, more comprehensive and indepth study is needed in future to come.